Prognosis and Biological Behavior of Gastric Signet-Ring Cell Carcinoma Better or Worse: A Meta-Analysis - Zhao, Shuai; Lv, Ling; Zheng, Kai; Tian, Yu; Zheng, Jian-Chun; Jiang, Cheng-Gang (Frontiers in Oncology, 2021)
Background The clinical pathology of gastric signet-ring cell carcinoma (SRC) is still unclear. This meta-analysis was performed to evaluate the difference in biological behavior and prognosis between SRC and non-signet ring cell carcinoma (NSRC). Methods A total of 58 eligible studies were analyzed using RevMan and other auxiliary software. Biological behaviors were compared based on odds ratio (OR) and mean difference (MD). Hazards ratio (HR) was calculated for prognosis based on Kaplan–Meier curves. Results Totally, 28,946 SRC patients were compared with 81,917 NSRC patients. Compared with NSRC patients, lower male: female ratio (OR = 0.53, P < 0.01), younger age (MD = −4.89, P < 0.01), more middle location (OR = 1.64, P < 0.01), more depressed type at early stage (OR = 1.31, P < 0.05), higher incidence of Borrmann type IV (OR = 1.96, P < 0.01), less lymph node metastasis at early stage (OR = 0.78, P < 0.05), better prognosis at early stage (HR = 0.59, P < 0.01), and worse prognosis at advanced stage (HR = 1.19, P < 0.01) were associated with SRC patients. Conclusion The prognosis of SRC at early stage is better than other types of gastric cancer, while that of SRC at advanced stage is relatively poorer.